2018
DOI: 10.1097/md.0000000000009776
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal adjustment after local resection of type 1 condylar osteochondroma

Abstract: To evaluate the feasibility of the orthodontic traction after local resection of the condylar osteochondroma (OC).From November 2011 to September 2016, consecutive patients with condylar OC who underwent orthodontic extraction after local resection of the mass were reviewed. Clinical data and cone-beam computed tomography (CT) were obtained before treatment (T0), 1 week after surgery (T1), and at least 6-month follow-up after OC resection (T2). Repeated-measures analysis of variance with Bonferroni multiple-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
1
1
Order By: Relevance
“…The measurements were changed from T1 to T2, showing the adaptive reconstruction process of the neo condyle. In the two sides, the AJS, SJS, PJS, and MJS vectors were increased in our study; however, these results were the opposite of those obtained in the study of Zhigui Ma, which showed decreases in AS and SS in OC-affected and unaffected sides [ 20 ]. This may be due to the different postoperative orthodontic methods used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The measurements were changed from T1 to T2, showing the adaptive reconstruction process of the neo condyle. In the two sides, the AJS, SJS, PJS, and MJS vectors were increased in our study; however, these results were the opposite of those obtained in the study of Zhigui Ma, which showed decreases in AS and SS in OC-affected and unaffected sides [ 20 ]. This may be due to the different postoperative orthodontic methods used.…”
Section: Discussioncontrasting
confidence: 99%
“…The maxillary and mandibular composite models were matched using bone tissue and 3D scanned tooth models, aligned into a common coordinate system, and then the facial soft-tissue model was also imported into ProPlan CMF 3.0 software (Materialise, Belgium). The measurements presented in our study were similar to those obtained using the method described by Ma, Zhigui [ 20 ]. The measurement system was described as follows: (1) The Frankfort horizontal (FH) plane was defined through the right and left orbitale (Or) and the midpoint of the bilateral porion (Po); (2) The midsagittal reference plane was defined as the plane perpendicular to the horizontal plane passing through the nasion and sella, and then adjusted through the mirror function; (3) The B, Go, Po, Pog, and Pog* points were marked on each side ( Figure 2 ).…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation